Metalloprotease Gp63-Targeting Novel Glycoside Exhibits Potential Antileishmanial Activity - Chakrabarti, Amrita; Narayana, Chintam; Joshi, Nishant; Garg, Swati; Garg, Lalit C.; Ranganathan, Anand; Sagar, Ram; Pati, Soumya; Singh, Shailja (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis (VL) and post kala-azar dermal leishmaniasis (PKDL) affect most of the poor populations worldwide. The current treatment modalities include liposomal formulation or deoxycholate salt of amphotericin B, which has been associated with various complications and severe side effects. Encouraged from the recent marked antimalarial effects from plant-derived glycosides, in this study, we have exploited a green chemistry-based approach to chemically synthesize a library of diverse glycoside derivatives (Gly1–12) and evaluated their inhibitory efficacy against the AG83 strain of Leishmania donovani. Among the synthesized glycosides, the in vitro inhibitory activity of Glycoside-2 (Gly2) (1.13 µM IC50 value) on L. donovani promastigote demonstrated maximum cytotoxicity with ~94% promastigote death as compared to amphotericin B that was taken as a positive control. The antiproliferative effect of Gly2 on promastigote encouraged us to analyze the structure–activity relationship of Gly2 with Gp63, a zinc metalloprotease that majorly localizes at the surface of the promastigote and has a role in its development and multiplication. The result demonstrated the exceptional binding affinity of Gly2 toward the catalytic domain of Gp63. These data were thereafter validated through cellular thermal shift assay in a physiologically relevant cellular environment. Mechanistically, reduced multiplication of promastigotes on treatment with Gly2 induces the destabilization of redox homeostasis in promastigotes by enhancing reactive oxygen species (ROS), coupled with depolarization of the mitochondrial membrane. Additionally, Gly2 displayed strong lethal effects on infectivity and multiplication of amastigote inside the macrophage in the amastigote–macrophage infection model in vitro as compared to amphotericin B treatment. Gp63 is also known to bestow protection against complement-mediated lysis of parasites. Interestingly, Gly2 treatment enhances the complement-mediated lysis of L. donovani promastigotes in serum physiological conditions. In addition, Gly2 was found to be equally effective against the clinical promastigote forms of PKDL strain (IC50 value of 1.97 µM); hence, it could target both VL and PKDL simultaneously. Taken together, this study reports the serendipitous discovery of Gly2 with potent antileishmanial activity and proves to be a novel chemotherapeutic prototype against VL and PKDL.